Mariana the Goldilocks fairy - Meadows, Daisy (London : Orchard Books, 2016)
Mariana the Goldilocks Fairy looks after the magical story of the Three Bears. But when Jack Frost steals her enchanted porridge spoon, the bears are replaced with horrid goblins! Rachel and Kirsty must get.
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction